Socialisation of student youth in social networks - T. Shcherban; O. Samoilov (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
Social networks have become a part of the daily life of students, they influence the development of views, values and identity, which can have an impact on students’ social connections, so research is an urgent task that contributes to understanding this influence. The purpose of the study was to investigate the impact of social networks on various spheres of life of modern students. In order to investigate the issues of socialisation of young people in social networks, the study used generalisation and analytical method. As a result, the importance of developing strategies aimed at strengthening the positive impact of social networks on students was highlighted. It was revealed that changing social norms and creating an atmosphere of open and decent communication in an online environment can help improve students’ socialisation in the virtual world. It was noted that the protection of privacy and the development of critical thinking are important for ensuring the security and information competence of social network users. The importance of developing media literacy and skills in verifying the truthfulness of information in the process of socialisation of students was noted. Strategies that promote the development of virtual space and improve interaction in social networks were outlined. The paper analysed aspects of positive socialisation of students in the digital age that help them solve problems and cope with the challenges of the online environment. The results of scientific research can contribute to a better understanding of how social networks affect young people, and help researchers develop programmes and strategies aimed at supporting the positive aspects of this impact and reducing possible negative consequences